ANALISIS MEMBANGUN PERSONAL BRANDING “BANG UCUP NIAGARA FRUIT” DI MEDIA SOSIAL TIKTOK: STRATEGI DAN DAMPAK - Laila, Kumi; Umairoh, Faikoh (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The phenomenon of bang ucup niagara fruit on social media tiktok increases the competitiveness of other fruit juice businesses. Its presence provides its own color for loyal customers and other people. With his viral figure on social media tiktok, researchers are interested in conducting more in-depth research. The purpose of this study is to determine the personal branding built by bang ucup on social media tiktok, strategies and impacts of personal branding. This research is qualitative descriptive, the key informant in this study is the social media tiktok bangucup niagara fruit. Data collection was carried out by observing content, documentation, interviews and literature studies. Interviews were conducted with followers who are also loyal customers of bangucup Niagara fruit. In this study, researchers tried to analyze the social media tiktok bangucup Niagara fruit with eleven classic personal branding concepts by Hubert k rampershad, then branding strategies including interaction with the audience and the content produced and the impact of branding on social media tiktok starting from sales and reputation generated.